The Failure Protection of Wireless-Based IIoT Technology for Fluid Level Control Systems - Sangsuwan, Thaksin; Thong-un, Natee; Pudchuen, Noppadol; Runglin, Kankrit; Wongsaroj, Wongsakorn (Trends in Sciences, 2022)
A novel protection mechanism was proposed for failure of a wireless-based IIoT system to control water level. Control via wireless communication can be executed safely using designed protection. A secondary path as a mesh network was automatically enabled to occur if the main MQTT network protocol failed. System backups were no longer required, with increased reliability of the wireless control network and low risk of failure. Performance control via the developed IIoT was demonstrated. Ability of the protection system to combat network failure was confirmed experimentally.